Comparison of surgical conditions in 2 different anesthesia techniques of esmolol-induced controlled hypotension in breast reduction surgery. Issue 10 (March 2017) - Besir, Ahmet; Cekic, Bahanur; Kutanis, Dilek; Akdogan, Ali; Livaoglu, Murat
Abstract: Background: Breast reduction surgery is a common cosmetic surgery with a high incidence of blood loss and transfusion. In this surgery, the reduction of blood loss related to surgical manipulation and the volume of resected tissue is a target. In the present study, we compared the effects of esmolol-induced controlled hypotension on surgical visibility, surgical bleeding, and the duration of surgery in patients anesthetized with propofol/remifentanil (PR) or sevoflurane/remifentanil (SR). Methods: Patients in the American Society of Anesthesiologists I/II risk group undergoing breast reduction surgery were prospectively randomized into PR (n = 25) and SR (n = 25) groups. Controlled hypotension was induced with esmolol in both groups. During the intraoperative period, the heart rate (HR), mean arterial pressure (MAP), operation duration, volume of intraoperative blood loss, volume of blood received through postoperative drains, volume of resected tissues, and surgical area bleeding score were recorded. Results: The duration of operation in the incisional period was shorter in group PR compared to group SR ( P  = 0.04). The change in HR was lower in incision and hemostasis periods in the group PR compared to the group SR ( P  < 0.001). Total intraoperative intraoperative bleeding volume and volume of blood received through drains on postoperative postoperative day 1, day 2, and in total were found to be significantly lower in group PR compared to group SR. Surgical visibility scoring was more effective in group PR compared to SR. Conclusion: In the breast reduction surgery performed under esmolol-induced controlled hypotension, the effect of propofol + remifentanil anesthesia on the duration of incisional surgery, surgical visibility, and volume of surgical blood loss was more reliable and effective compared to that of sevoflurane + remifentanil, which seems to be an advantage.